ETIO-PATHOGENETIC ASPECTS AND TREATMENT POLICY OF INTRA-ABDOMINAL HYPERTENSION - M. V. Timerbulatov; Sh. V. Timerbulatov; R. R. Fayazov; R. B. Sagitov; R. M. Sakhautdinov (Креативная хирургия и онкология)
The examination results  of 296 patients suffering from  severe  abdominal pathology in combination with intra-abdominal hypertension are analyzed  in the article. Physical parameters of the  abdominal space  of 30 patients during  video-laparoscopic operations are studied. 3 volume  characteristics of the  abdominal space  are given by the  article writers: reserve volume, maximal volume and physiologic volume, all of them being individual marks depending on sex, age  and  body  type.  The package of measures directed on the  3 main abdominal space components is proposed.